Metabolic and anti‐inflammatory effects of a home‐based programme of aerobic physical exercise. Issue 12 (December 2013) - Di Raimondo, D.; Tuttolomondo, A.; Buttà, C.; Casuccio, A.; Giarrusso, L.; Miceli, G.; Licata, G.; Pinto, A.
Summary Aims Regular exercise demonstrated the ability to provide enormous benefits to many diseases, atherosclerotic‐based, degenerative and neoplastic, but also to grant anti‐inflammatory actions, assessed by various authors in different populations. Despite of these clear benefits, many patients are unable to attain long‐term results through chronic physical activity for different causes. On this basis, the aim of our study was to assess the metabolic and anti‐inflammatory effects of a home‐based programme of fast walking in patients affected by metabolic syndrome (MS). Materials and methods We enrolled 176 subjects with MS as stated by ATP III criteria. Patients were invited to walk for 1 h every day 5 days a week for 24 weeks. The walking velocity was required higher than the one retained 'comfortable' by the patient, previously assessed in the run‐in visit. Monitoring of physical activity was carried out through an OMRON step counter type Walking Style II. All the subjects enrolled completed the training period. Results After the 24 weeks of intervention body mass index changed from 31.59 to 29.23 (p < 0.001); mean waist circumference passed from 105.19 to 100.06 cm (p < 0.001); mean fasting glucose changed from 119.76 to 114.32 mg/dl (p < 0.001); for diabetic population (n = 70) mean glicated haemoglobin levels changed from 7.38% to 6.86% (p < 0.001); total cholesterol levels from 192.15 to 185.78 mg/dl (p < 0.001); HDL cholesterol levels raised from 44.03 to 47.63 mg/dl (p < 0.001); triglycerides levels lowered from 148.29 to 135.20 mg/dl (p < 0.001); WBC changed from 7361.08 to 7022.56/mm3 (p < 0.001); hs‐CRP from 0.55 to 0.28 mg/dl (p < 0.001); fibrinogen serum levels lowered from 339.68 to 314.86 mg/dl (p < 0.001). Conclusions A long‐term home‐based programme of aerobic physical activity improves metabolic asset and reduces systemic inflammation in sedentary people.